Metabolism Analysis of Alantolactone and Isoalantolactone in Rats by Oral Administration - Mengyue Wang; Renjie Xu; Ying Peng; Xiaobo Li (Journal of Chemistry)
Alantolactone and isoalantolactone are the major active ingredients of Inulae Radix. Their metabolism in vivo and in vitro was investigated by UPLC-Q-TOF-MS for the first time. As a result, nine metabolites in vivo including cysteine conjugates, oxidates, dehydrogenates, and hydrates were detected in rat bile after oral administration. The metabolites produced in vitro by incubation with rat liver microsomes were found to be substantially identical to those detected in vivo. However, no metabolites were detected in the samples of plasma, feces, and urine or in the incubates of gastric juice, intestinal juice, and intestinal bacteria. These results reveal that the liver is the main metabolic organ for alantolactone and isoalantolactone, and the first pass effect of the liver appears to be the reason for the low oral bioavailability of the two lactones.